2022
DOI: 10.3390/ijms23115958
|View full text |Cite
|
Sign up to set email alerts
|

Colonization and Infection of Indwelling Medical Devices by Staphylococcus aureus with an Emphasis on Orthopedic Implants

Abstract: The use of indwelling medical devices has constantly increased in recent years and has revolutionized the quality of life of patients affected by different diseases. However, despite the improvement of hygiene conditions in hospitals, implant-associated infections remain a common and serious complication in prosthetic surgery, mainly in the orthopedic field, where infection often leads to implant failure. Staphylococcus aureus is the most common cause of biomaterial-centered infection. Upon binding to the medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 185 publications
1
37
0
3
Order By: Relevance
“…This study showed that nanogel are more effective on P. aeruginosa than on S. aureus . The cell surface of S. aureus has a negative net charge [ 53 ]. As CMC is negatively charged, it seems proper interaction between nanogel and the bacterial membrane did not occur; however, it should be checked in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that nanogel are more effective on P. aeruginosa than on S. aureus . The cell surface of S. aureus has a negative net charge [ 53 ]. As CMC is negatively charged, it seems proper interaction between nanogel and the bacterial membrane did not occur; however, it should be checked in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The process of plasma proteins attaching to the biomaterial’s surface is governed by the physical and chemical properties of the material surface such as polarity and roughness of the material, as well as the characteristics of the plasma proteins such as size and charge [ 41 ]. After being attached to the surface of biomaterials, these proteins form an ideal scaffold which provides a foothold for bacterial adhesion and subsequent proliferation [ 14 ]. For this purpose, staphylococci have evolved a series of cell wall-anchored (CWA) proteins, of which the best-characterized group is called MSCRAMMs (microbial surface components recognizing adhesive matrix molecules) [ 42 , 43 ], each specifically binding to ECM proteins covering the devices.…”
Section: Staphylococcal Biofilm Developmentmentioning
confidence: 99%
“…Clinical practice and experimental studies indicated clearly that in most cases, antibiotic therapy alone is insufficient to eradicate biofilm infection, and implants infected by bacteria usually require surgical resection [ 12 , 13 ]. In addition, it must be mentioned that each surgery to replace failed implants has a higher risk of recurrence (up to 30%) than that of the initial operation [ 14 ]. To solve these problems, great research progress has been made in the therapeutic approaches of biofilm, such as the studies on surface modification of implants, phage therapy, vaccine technology, and nanomedicines, but these new treatment methods need further preclinical and clinical validation before they are widely promoted for clinical use [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many of these infections are iatrogenic, meaning they are acquired through medical examination or treatment. S. aureus is notorious for contaminating medical devices 18–20 . Given the increased usage of medical devices in our healthcare systems, this public health crisis is only expected to worsen.…”
Section: Introductionmentioning
confidence: 99%
“…S. aureus is notorious for contaminating medical devices. [18][19][20] Given the increased usage of medical devices in our healthcare systems, this public health crisis is only expected to worsen. Concurrently, S. aureus bacteria are known to develop resistance to antibiotics that have historically been used to treat them.…”
mentioning
confidence: 99%